Invitation to astrophysics - Padmanabhan Thanu (World Scientific, 2006)
This unique book provides a clear and lucid description of several aspects of astrophysics and cosmology in a language understandable to a physicist or beginner in astrophysics. It presents the key topics in all branches of astrophysics and cosmology in a simple and concise language. The emphasis is on currently active research areas and exciting new frontiers rather than on more pedantic topics. Many complicated results are introduced with simple, novel derivations which strengthen the conceptual understanding of the subject. The book also contains over one hundred exercises which will help students in their self study.
Keywords: Astrophysics; Cosmology